Impact of International Tourists’ Co-creation Experience on Brand Trust, Brand Passion, and Brand Evangelism - Nkoulou Mvondo, Gustave Florentin; Jing, Fengjie; Hussain, Khalid; Jin, Shan; Raza, Muhammad Ali (Frontiers in Psychology, 2022)
Drawing on the theory of engagement, the present study aims to examine the outcomes of the co-creation experience in a realistic co-creation setting, a hotpot restaurant. To this end, the current research links the relationship marketing literature to hospitality and tourism research and formulates a novel framework by incorporating tourists' co-creation experience, brand evangelism, brand trust, and brand passion in an integrated conceptual model. Using a quantitative research design, a total of 453 international tourists were surveyed in China. The findings revealed that co-creation experience dimensions positively impact brand evangelism, trust, and passion. Additionally, we found that brand trust and brand passion positively affect brand evangelism. We also confirmed the mediating effect of brand trust and brand passion in bridging the co-creation experience and brand evangelism. This study offers valuable insights for restaurant brand managers regarding attracting and engaging foreign travelers with their service businesses.